Pengaruh literasi keuangan masyarakat terhadap minat berinvestasi dan upaya pembinaannya - Istiqlaliyah Muflikhati; Irni Rahmayani Johan; Lilik Noor Yuliati; Pudji Muljono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The decline in people's income causes their financial prosperity. This can occur due to a lack of public awareness in managing finances for the future or a lack of interest in investing. This research aims to analyze the influence of financial literacy (knowledge, attitudes and behavior) on investment interest. This research is a quantitative descriptive study involving 205 respondents who met the criteria, namely adults and not yet invested. Sampling was carried out using voluntary sampling techniques from people who were willing to become respondents. The data collected is primary data obtained directly from respondents by filling out an online questionnaire. The research results show that the respondents' financial knowledge is in the low category, while the respondents' financial attitudes and behavior are in the medium category. The investment interest of all respondents is in the low category. The results of the analysis also show that investment interest is directly influenced by financial knowledge and financial attitudes. Financial knowledge has an indirect influence on investment interest, namely through financial attitudes. It is hoped that the public can increase their financial literacy and interest in investing through socialization, advocacy and mentoring programs.